REVITALIZING THE TEACHING AND LEARNING PROCESS WITH ARTIFICIAL INTELLIGENCE APPLICATIONS - Loso Judijanto; Syarif Hidayatullah; Zulvia Trinova (CV. ADIBA AISHA AMIRA, 2024)
The development of artificial intelligence (AI) technology has opened up new opportunities in various sectors, including education. This study uses the literature research method. The results show that the integration of AI in the teaching and learning process has significant potential to improve learning personalization, assessment effectiveness, and education management efficiency. AI can facilitate adaptive learning, provide real-time feedback, and assist educators in identifying students' individual learning needs. However, AI implementation also faces challenges such as the need for adequate technological infrastructure, improving educators' digital competencies, and ethical and data privacy issues